Cloning of Cystatin II gene isolated from some maize samples in Vietnam - Xuan Thuy, Vi Thi; Tuong, Ho Manh; Son, Le Van; Thanh Thanh, Nguyen Vu; Mau, Chu Hoang (Academia Journal of Biology, 2014)
Cystatin is the protein inhibitor of cysteine ​​proteinase activity, it roles as a substrate into the active center of cysteine ​​proteinase, that prevents the other substrate proteins go into. In this report, we present the results of isolation, cloning and determination of the cystatin II gene sequence of four local maize samples (SL, LC1, LC2, LC3) and CP888 maize cultivar. The coding region of cystatin II gene isolated from some maize samples had the size of 405 nucleotides, coding 134 amino acids. The comparative results of amino acid sequences of deductive protein of five maize samples and cystatin (code number D38130) in GenBank showed that there were 22 different amino acids, and no difference in the CY region. The cystatin II gene can be used to develop transformation vector for genetic engineering of maize to resist to maize weevil.